Correlation of Parenting with Religious Awareness and Its Implications for Counseling - Syarifah Syarifah; Kasmuri Salamat (International Journal of Research in Counseling, 2022)
This research is motivated by various levels of religious awareness of students and inequality in parenting patterns in educating children. This study aims to see the relationship between parenting and religious awareness and its implications in counseling. The research approach used correlation research with a sample of 73 students. The data collection tools used are the scale of religious awareness and parenting.  The data analysis used anlysis product moment correlation.  The results of the study found that there was a significant relationship between parenting and religious awareness. The relationship between the two is in the low category. Meanwhile, separately, there is a relationship between democratic parenting and the religious basis of students and is in the moderate category. As for authoritarian and permissive parenting, there is no significant relationship. Implications in counseling counseling counselors can use various service techniques that are in accordance with the client's cultural conditions and one of them is through islamic approach counseling.